AM fungi and rhizobium regulate nodule growth, phosphorous (P) uptake, and soluble sugar concentration of soybeans experiencing P deficiency. (9th November 2016) - Ding, Xiaodong; Zhang, Shirong; Wang, Rongping; Li, Shuyi; Liao, Xinrong
ABSTRACT: To understand the mechanisms behind the beneficial combinations of the existence and formation processes of tripartite symbiosis of arbuscular mycorrhizal fungi (AMF) and nitrogen (N)-fixing rhizobia in phosphorus (P) deficiency. The effects of different inoculations of Bradyrhizobium japonicum (BJ) and Glomus mosseae (GM) on plant growth, P uptake, and soluble sugar concentration of soybeans in a P-deficient environment were investigated utilizing split-root systems supplemented with either KH2 PO4 (0.01 mM, I-P) or Phytin (200 mg P kg −1, O-P) for 56 days. Six treatments were applied: (1) mono-inoculation of BJ in organic P compartment, O-BJ; (2) mono-inoculation of BJ in inorganic P compartment, I-BJ; (3) mono-inoculation of BJ in organic P compartment and mono-inoculation of GM in inorganic P compartment, O-BJ/I-GM; (4) mono-inoculation of BJ in inorganic P compartment and mono-inoculation of GM in organic P compartment, O-GM/I-BJ; (5) dual inoculation of BJ and GM in organic P compartment, O-BJ/GM; and (6) dual inoculation of BJ and GM in inorganic P compartment, I-BJ/GM. Compared with sole inoculation of BJ, dual inoculation increased the plant and nodule biomass, which were higher in I-BJ/GM and O-BJ/I-GM treatments compared to O-GM/I-BJ and O-BJ/GM treatments. Roots inoculated with GM in I-P grew better regardless of whether BJ was inoculated or not. GM inoculation in I-P also increased the number of leaves and the rate of photosynthesis. Nodule P concentration following dual inoculation in I-P was increased 2.1-fold compared to that in sole inoculation with BJ. Shoot soluble sugar concentration with dual inoculation in O-P was less than that in the other three treatments. Inoculated with GM in I-P increased the root soluble sugar concentration compared with the non-GM plants or GM inoculation in O-P. The present findings may explain a regulatory system for the nutrition of beneficial microbial interactions by the nodule or by AM fungal hyphae at selecting the best performing tripartite symbiotic partners in P deficiency.